2004
DOI: 10.1111/j.1440-1703.2004.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sika deer on tree seedlings in a warm temperate forest on Yakushima Island, Japan

Abstract: High-density herbivore species often play an important role in forest regeneration. Native sika deer ( Cervus nippon yakushimae ) inhabit a high density (51.5-63.8 head/km 2 , estimated by a pellet count method) area in the western part of a lowland natural forest on Yakushima Island, Japan. To test experimentally the impact of sika deer on the mortality and the survivability of current-year seedlings, which are at a more vulnerable stage than the later stages, we constructed fenced exclosures, planted seeds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…The annual mean temperature is approximately 21 °C, which corresponds to the transition between subtropical and warm temperate zones (Tagawa 1994). Annual precipitation is approximately 2600 mm (Tagawa 1980 (Tsujino and Yumoto 2004).…”
Section: Study Area and Fecal Sample Collectionmentioning
confidence: 99%
“…The annual mean temperature is approximately 21 °C, which corresponds to the transition between subtropical and warm temperate zones (Tagawa 1994). Annual precipitation is approximately 2600 mm (Tagawa 1980 (Tsujino and Yumoto 2004).…”
Section: Study Area and Fecal Sample Collectionmentioning
confidence: 99%
“…In recent years, deer (Cervidae) populations have increased dramatically throughout many areas of the world, including North America (Horsley et al 2003), Europe (Apollonio et al 2010), Asia (Tsujino andYumoto 2004, Suzuki et al 2008), and Oceania (Platt et al 2004, Husheer et al 2006. Population increases have been driven primarily by forest clearing (Dale 1997), reduction of predator populations (Mladenoff et al 1999), and milder winter temperatures (Dumont et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported the disturbance of regeneration of tree species by ungulate browsing around the world (Wilson 1969, Gill 1992, Waller and Alverson 1997, Potvin et al 2003, Rooney and Waller 2003, Senn and Suter 2003, Weisberg and Bugmann 2003, Cote et al 2004, Tsujino and Yumoto 2004, Pepin et al 2006, Takatsuki 2009, Hidding et al 2012, Nagaike et al 2014Cutini et al 2015, Swiss Federal Institute for Forest 2015; a few studies were carried out on the dynamics and the other ecological issues of roe deer in Korea (Kim and Kim 2001, Kim 2006, Kim and Hong 2006, Kim et al 2007a, Jeon and Kim 2011, Jo et al 2012, 2013, Kang 2013. In addition, studies on the dynamics of forest stands indicated that competition with other species of understory vegetation such as dwarf bamboo (genus Sasa) can interrupt the establishment of the seedlings of the natural tree species at forest stands of the world (Nakashizuka 1988, Peters et al 1992, Abe et al 2001, Taylor et al 2004, 2006, Doležal et al 2009, Song et al 2014.…”
Section: Introductionmentioning
confidence: 99%